Cervical Epidural Spinal Analgesia for Acute Management of Severe Unilateral Forelimb Lameness: Case Report - Watkins, Amanda R.; Hopster, Klaus; Levine, David; Hurcombe, Samuel D. (Frontiers in Veterinary Science, 2021)
A 20-year-old Quarter Horse gelding was presented with severe right forelimb lameness (5/5 AAEP Lameness Scale) due to a tear of the superficial digital flexor muscle which was diagnosed via palpation of swelling and ultrasonography revealing major muscle fiber disruption and hematoma formation. When traditional systemic therapy (non-steroidal anti-inflammatories) did not restore clinically acceptable comfort and the risk of supporting limb laminitis became a reasonable concern, a cervical epidural catheter was placed between the first and second cervical vertebrae in the standing, sedated patient using ultrasound guidance. The gelding was treated with epidural morphine (0.1 mg/kg every 24 hours then decreased to 0.05 mg/kg every 12 hours) and was pain-scored serially following treatment. Spinal analgesia was provided for three days. Pain scores significantly decreased following each treatment with morphine and the gelding was successfully managed through the acutely painful period without any adverse effects associated with the C1-C2 epidural catheter placement technique, the epidural morphine or contralateral limb laminitis. At 2 month follow up the gelding was walking sound with no complications seen at the catheter insertion site. In this case, spinal analgesia using epidural morphine administered via a cervical epidural catheter was an effective and technically achievable option for pain management associated with severe forelimb muscle injury in a horse.